x − 1 a x 2 − 2 4 x + b = x 2 + x
If the equation has exactly two distinct real solutions (of x ) and their sum is 12 then find the value of a − b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way.
Why it can be only factored as ( x − m ) 2 ( x − n )
Log in to reply
Since a cubic equation has always 3 solutions and question says that it has 2 which is only possible when two of the three solutions are coincident i.e of the form m,m,n.
Let a = 1 1 and b = − 3 5 . Then the given equation becomes x 2 − 1 1 1 x 2 − 2 4 x + 3 5 = x . Then ( x + 1 ) ( x − 1 ) ( x + 1 ) ( 1 1 x − 3 5 ) = x , so x − 1 1 1 x − 3 5 = x . Then 1 1 x − 3 5 = x ( x − 1 ) ⇒ x 2 − 1 2 x + 3 5 = 0 . The solutions are 5 and 7, so a = 1 1 and b = − 3 5 also work.
Also ( 1 3 , 1 1 ) works the above way but gives x = 1 as solution which we have to then reject. So it doesnot work
With x 3 − a x 2 + 2 3 x − b = 0 ,
a = 2 α + γ
23 = α 2 + 2 α γ
b = α 2 γ
12 = α + γ
α 2 − 2 4 α + 2 3 = 0
α = 1 and γ = 1 1 OR α = 2 3 and γ = − 1 1
Original equation takes only α = 2 3 and γ = − 1 1 for x = α = 1
a = 4 6 − 1 1 = 35
b = 2 3 2 × ( − 1 1 ) = -5819
a - b = 35 + 5819 = 5854
answer: 5 8 5 4
Problem Loading...
Note Loading...
Set Loading...
Rearranging the equation gives
x 3 − a x 2 + 2 3 x − b = 0 .
We know that this equation has exactly two distinct real solutions. If we call them m and n , the equation above is equivalent to
( x − m ) 2 ( x − n ) = 0 ,
which can be written:
x 3 − ( 2 m + n ) x 2 + ( m 2 + 2 m n ) x − m 2 n = 0 .
By comparing the coefficients in the equations above we obtain
a = 2 m + n
2 3 = m 2 + 2 m n
b = m 2 n .
We are given that m + n = 1 2 , so together with m 2 + 2 m n − 2 3 = 0 we now have two equations with two unknowns. The quadratic equation involved gives us two pairs of solutions:
m = 2 3 , n = − 1 1
and
m = 1 , n = 1 1 .
However, because the solution m = 1 implies division by zero in the original equation, this solution must be dismissed.
By inserting m = 2 3 and n = − 1 1 we get:
a = 2 m + n = 3 5
b = m 2 n = − 5 8 1 9 .
Thus, we have a − b = 5 8 5 4 .